Random Number Generation with LFSR Based Stream Cipher Algorithms - Tuncer, Taner; Avaroglu, Erdinc (Ieee, 2017)
Random numbers have a wide range of usage area such as simulation, games of chance, sampling and computer science (cryptography, game programming, data transmission). In order to use random numbers in computer science, they must have three basic requirements. First, the numbers generated must be unpredictable. Second, the numbers generated should have good statistical properties. Finally, the generated number streams must not be reproduced. Random number generators (RNGs) have been developed to obtain random numbers with these properties. These random number generators are classified into true random number generators (TRNG) and pseudo random number generators (PRNG). One of the PRNGs used for generate random numbers is Stream Encryption algorithms. In this paper, random number generation of LFSR based stream encryption algorithms and their hardware implementations are presented. LFSR based stream encryption algorithms have been implemented on Altera's FPGA based 60-nm EP4CE115F29C7 development boards by using VHDL language. The obtained random numbers passed the NIST statistical tests, accepted as standard for cryptographic applications.
40th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) -- MAY 22-26, 2017 -- Opatija, CROATIA